Suluk as Social Piety: Phenomenological Studies at the Naqsabandiyah Khalidiyah Sufi Order In Sokaraja Banyumas - Nasrudin Nasrudin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2021)
Suluk is the most important ritual in the Sufi order by zikr and getting closer to the Creator, usually by leaving the activities public. However, there are data and facts that prove that Suluk actually encourages active efforts to improve the community's social life. The Naqshabandiyah Khalidiyah Sokaraja Banyumas Order is one of the Sufi order that pays attention to suluk, which is carried out in peguron by a spiritual guide for ten to forty days. Consistency in carrying out the practice and discipline will make a pious person mentally-spiritually so that he becomes an example in the social life of the community. Sometimes it creates a negative stigma against Sufi order, but Suluk gives birth the benefits of improving spiritual and social qualities. Suluk is not isolating from social life just for worship absolutely without limits, but becoming a medium of self-purification to become a Muslim who has mental and spiritual readiness to live a better in the midst of social life with social piety.